Experimental investigation of thermomechanical behaviour of clay-rich sandstone at extreme temperatures followed by cooling treatments. (July 2018) - Rathnaweera, T.D.; Ranjith, P.G.; Gu, X.; Perera, M.S.A.; Kumari, W.G.P.; Wanniarachchi, W.A.M.; Haque, A.; Li, J.C.
Abstract: The aim of this study is to investigate the influence of extreme temperatures (from 25° to 1000°C) followed by two cooling methods (both rapid and slow) on the mechanical behaviour of clay-rich Hawkesbury sandstone under uniaxial conditions. A separate set of samples was tested under continuous heating conditions without cooling to compare the results with those for cooled samples. The stress-strain behaviours were analysed, with simultaneous recording of the acoustic signals and the failure mode. Scanning electron microscopy (SEM) and X-ray diffraction (XRD) analyses were also performed to understand the changes observed in the mechanical tests. According to the results, the mechanical, mineralogical and microstructural characteristics of clay-rich sandstones are largely dependent on the thermal field, and, regardless of the cooling method, the compressive strength, Young's modulus, crack initiation stress and crack damage stress appear to increase when the preheating temperature increase from 25 °C to 600 °C and decrease with increasing preheating temperature for temperatures greater than 600 °C. The SEM results confirmed the transformation of the initial hexagonal kaolinite mineral structure into a fibre-like (needle-type) mineral structure, which is believed to be the reason for the strengthening phenomenon observed at preheated temperatures between 25 °C and 600 °C. Progressive dehydroxylisation of kaolinite in the sandstone cement at temperatures beyond 600 °C was found to be the main reason for the weakening and softening of the sandstone which was observed with increasing preheated temperature beyond 600 °C. Apart from these mineral degradations, induced inter-granular and intra-granular cracks at preheated temperatures beyond 600 °C also play a dominant role in the weakening of clay-rich sandstone.